Gurus in America - Forsthoefel, Thomas A.; Humes, Cynthia Ann, 1958- (SUNY series in Hindu studies., 2005)
"Gurus in America provides an excellent introduction to the guru phenomenon in the United States, with in-depth analyses of nine important Hindu gurus - Adi Da, Ammachi, Mayi Chidvilasananda, Gurani Anjali, Maharishi Mahesh Yogi, Osho, Ramana Maharshi, Sai Baba, and Swami Bhaktivedanta. All of these gurus have attracted significant followings in the U.S. and nearly all have lived here for considerable periods of time. The book's contributors discuss the characteristics of each guru's teachings, the history of each movement, and the particular construction of Hinduism each guru offers. Contributors also address the religious and cultural interaction, translation, and transplantation that occurs when gurus offer their teachings in America. This is a guide that will elucidate an important element in America's diverse and ever-changing spiritual landscape."--Jacket